konsumsi KONSUMSI DAN KECERNAAN PROTEIN KASAR PAKAN SAPI BALI JANTAN YANG DIBERI COMPLETE RUMEN MODIFIER - Syafiq, Muhammad; Suhartati, Fransisca Maria; Yuwono, Pambudi (ANGON: Journal of Animal Science and Technology, 2024)
ABSTRACT Research aimed to examine the effect of giving Complete Rumen Modifier on the intake and digestibility of Crude Protein (CP) feed of Bali bulls. The material used is 3 male Balinese cows, the feed given consists of concentrate 2% of the cow's body weight and voluntary feed intake hay. The concentrate is composed of onggok 38,58%, rice bran 14,29%, coconut cake 13,14%, palm cake 10%, pollard 9,43%, molasses 4,86%, coffee husk 4,8%, dolomite 1,43%, aminosine 1,2%, salt 0,86%, urea 0,86%, zeolite 0,57%, and minerals 0,28%. The composition of CRM consists of noni leaf flour 30%, cassava vine leaf meal 30%, dry tea pulp 30%, Saccharomyches cerevisiae 3%, methionin 2%, urea 1% and sulfur 4%. The research used the experimental method of Latin Square Design, there were three treatments tested, namely P0 (concentrate 2% body weight cow and straw voluntary feed intake), P1 (P0 + CRM 0.5% from Dry Matter concentrate), and P2 (P0 + CRM 1% from concentrate). The variables measured are intake and Digestibility of crude protein, the data obtained were tested using analysis of variance and differences in treatment with the Orthogonal Polynomial test. The results of the analysis of variance showed that the treated feed given CRM had no significant effect (P>0.05) on PK digestibility. Meanwhile, PK consumption had a significant effect (P<0.05) on feed treated with P1 and P2 compared to P0. The conclusion obtained from this study is that the provision of CRM can increase consumption of PK while the digestibility of PK decreases when given CRM.